A Study on Biogas Production Potential in Thailand 2019 - Saran Khotmanee; Unnat Pinsopon (My University, 2021)
Thailand 2015 Alternative Energy Development Plan (AEDP2015) stated that renewable energy should take part in the gross energy consumption for 30% by the year 2036. The plan also targeted compressed biogas to replace refined petroleum for a daily use 4,800 tons, as well as the biogas produced from waste to be the source for a 600 MW electricity power generation. To understand how close the biogas production status is up to the plan, the biogas production potential in Thailand 2019 was investigated, and is presented in this paper. The biogas production potential was considered from 3 sectors: industrial plants, livestock, and agricultural plants. The industrial plants with high organic content of waste were considered in the study. They are ethanol, starch, palm oil, rubber, food and alcoholic beverage plants. Livestock investigated in this study are cattle, buffaloes, pigs and chickens. Top 6 most cultivated agricultural plants were considered: rice, corn, sugarcane, cassava, palm and pineapple. Only business units with significant production potential yields were included in the potential study. The biogas productivity status in the year 2019 was also surveyed. The biogas production potential in Thailand 2019 was estimated to be 22,827 million m 3 , higher than the planned demand of 8,124 million m 3 in the year 2036 due to the AEDP2015 plan. However, the productivity status was found to be 816 million m 3 , only 10% of the planned value in the year 2036. Continual supports from the government are needed in order that the biogas productivity could meet the targeted demand in the year 2036.
Keywords: Anaerobic Digestion and Biogas Production; Water-Energy-Food Nexus Studies; Hybrid Renewable Energy Systems